Effects of pyroligneous acid on life history and physiology of two pyralid pests of stored products. (May 2022) - Homayoonzadeh, Mohammad; Talebi, Khalil; Torabi, Ehssan; Allahyari, Hossein; Nozari, Jamasb; Scully, Erin D.
Abstract: Natural products derived from plant materials, such as wood vinegar (pyroligneous acid; PA), have shown toxicity to insects in previous studies; however, the impact of this substance on physiology and life history of stored product insects is unknown. Thus, the current study aimed to determine the effects of PA on two prominent stored product moths, Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae) and Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae). LC50 /24h values of PA were determined for both species and first instar larvae were fed on an artificial diet containing LC50 concentrations of PA for their entire life cycle. Final instar larvae were selected for biochemical analysis while life history parameters were assayed in female adults that emerged from treated larvae. In both species, significantly lower activities of digestive enzymes (α-amylase, protease, and lipase) and detoxifying enzymes (carboxylesterase, monooxygenase cytochrome P450, and glutathione S-transferase) were observed in treated larvae relative to untreated larvae. In contrast, antioxidant enzyme activities (superoxide dismutase, phenoloxidase, and ascorbate peroxidase) were significantly elevated in treated larvae compare to controls in both species. Moreover, larvae of both species tended to have lower levels of energy reserves, such as proteins, lipids, and carbohydrates, and adults exhibited reduced longevity, fecundity, and oviposition periods in comparison to untreated larvae. Finally, GC-MS analysis of the PA used for this study demonstrated that phenolic compounds and organic acids were the largest constituents. These results indicate that consumption of PA leads to the induction of to the antioxidant system, the inhibition of detoxification and digestion enzyme activities as well as reduced levels of energy reserves. Cumulatively, these effects resulted in reduced longevity and fecundity compared to control insects. This study expands our knowledge of the impacts of PA on physiology and life history for two prominent pests of stored products. Highlights: Pyroligneous acid (PA) has shown toxicity to Mediterranean flour moth (MFM) and Indian meal moth (IMM). Larvae of MFM and IMM fed on a treated diet with LC50 of PA showed increased activity of antioxidant enzymes as well as lower activities of digestive and detoxifying enzymes. Reduced fitness and lower energy reserves were also observed in treated larvae. GC-MS analysis of the PA demonstrated that phenolic compounds and organic acids were the largest constituents.